Developing methods of assisted natural regeneration for restoring foundational desert plants. Issue 2 (2nd April 2020) - Abella, Scott R.; Chiquoine, Lindsay P.; Weigand, James F.
Abstract: Assisted natural regeneration (ANR) is a restoration and management technique for enhancing the natural recruitment of desired species. To test ANR strategies in an arid environment, we applied irrigation and shelters to natural seedlings of the ecologically foundational shrub Larrea tridentata to enhance revegetation of a disturbed site in the Mojave Desert, USA. Irrigation did not improve seedling survival and growth. Shelters reduced 2-year survival by 31% but tripled height growth of surviving seedlings. Utility of shelter for ANR thus hinged on uncertain tradeoffs among seedling survival, height growth, and implementation costs. Mixed results suggest that further evaluating other combinations of treatments and with different species is required to understand ANR's potential for restoration in arid lands.